O13 End-stage liver disease aetiology impacts on the site and severity of muscle weakness in patients awaiting Liver Transplantation: A prospective case-control study. (20th September 2022) - Dhaliwal, Amritpal; Quinlan, Jonathan; Williams, Felicity; Allen, Sophie; Nicholson, Thomas; Choudhary, Surabhi; Breen, Leigh; Lavery, Gareth; Greig, Carolyn; Lord, Janet; Elsharkawy, Ahmed; Armstrong, Matthew
Abstract : Introduction: Patients with ESLD are at increased risk of sarcopenia (loss of L3 muscle mass on imaging) and reduced transplant-free survival. Despite this, there remains a paucity of aetiology-specific data on the site and type of muscle dysfunction in ESLD. Our prospective case-control study aimed to evaluate differences in muscle mass, quality and strength in ESLD compared to healthy controls, with analysis for different aetiologies of ESLD. Methods: Patients with ESLD were recruited from the out-patient Birmingham Liver Unit (UK) and compared to age/sex matched healthy controls. Lower limb assessment included quadriceps volume index (cm3/m2)and intermuscular adipose tissue (IMAT (%); myosteatosis) measured by MRI, and maximal (non-dominant) isokinetic leg extension peak torque (Nm) via dynamometry. Upper limb assessment used mid arm muscle circumference (MAMC (cm)) and peak dominant handgrip strength (HGS (kg)) via dynamometry. Results: Forty-two patients with ESLD (62% male; mean age 55 years; MELD 13; Childs-Pugh 8) were studied. Disease aetiologies were ArLD 47.6%, immune-mediated (AIH, PSC, PBC) 33.3%, and NAFLD 14.2%. Prevalence of hepatic encephalopathy, portal hypertension and ascites were 57.1%, 90.1% and 73.8%, respectively. Muscle mass: Quadriceps volume index was lower in ESLD than controls (348.9±71.6 vs 409.3±107.0 cm3/m2, p<0.05), but there was no difference for MAMC. There were no differences in either quadriceps volume index [ figure 1a ] or MAMC between disease aetiologies. Muscle quality: The mean IMAT percentage was higher in ESLD than controls (10.6±3.5% vs 5.2±1.8%, P<0.0001), with similar amounts of myosteatosis in all disease aetiologies [ figure 1b ]. Muscle strength: Leg extensor peak torque was lower in ESLD compared to controls (100.9±36.6 vs 142.5±51.0 Nm, p<0.001), with the lowest lower limb strength reported in patients with ArLD (96.7±30.3, p<0.001 vs. control) [ figure 1c ]. HGS was lower in ESLD compared to control (33.0±8.5 kg vs 39.4±10.7 kg, p<0.05), with the lowest upper limb strength found in patients with NAFLD (26.2±8.6 kg, p<0.05 vs. control males) [ figure 1d ]. Conclusion: Muscle mass, quality and strength are significantly reduced in the lower limbs (quadriceps) of patients with ESLD. Even though reductions in muscle mass and quality are similar, the aetiology of ESLD impacts on the site and severity of muscle weakness. Future interventions and 'fitness for transplant' assessments need to address these disease-specific differences.